Policy Capacity in The Policy of Structuring General Functional Positions in The Government Environment - Restu Agung Firdaus; Baiq Dessyazizah Destianikitha; Eko Supeno (Politeknik Siber Cerdika Internasional, 2023)
This study aims to analyze the policy capacity in the employee management policy in the General Functional Class in the Government of Bangkalan Regency. The problem is that the availability of position classes has not been accommodated in the Regent Regulation Number 75 of 2020 for several job classes. This raises problems such as placing employees in a lower position class than they should be, several job classes are still not fulfilled, causing jealousy between employees. This study uses the theory of policy capacity by Xun Wu, Ramesh, and Howlett with 3 (three) indicators, namely analytical capacity, operational capacity and political capacity at each level, both individual, organizational and system. The research was conducted using a qualitative research method with a descriptive type to dig deeper and detailed information. The location of the research was carried out in the Organizational Section of the Regional Secretariat of Bangkalan Regency. Sources of information or informants that are relevant to the topic in this study are from the Organizational Section, the Staffing and Human Resources Development Agency, the Education Office, the Environment Service. The use of data in this study comes from primary and secondary data collected through interviews, observation and the use of other supporting documents.